2021
DOI: 10.1108/ijoem-08-2020-0924
|View full text |Cite
|
Sign up to set email alerts
|

A financial restatement, media attention and stock idiosyncratic risk in the Chinese stock market

Abstract: PurposeThis paper aims to enrich the scope of the influence of media reports on the stock risk, and it also provides a path to support the research on the relationship between media reports and idiosyncratic risks in the stock market.Design/methodology/approachThe authors select financial restatement samples of listed companies in China from Jan 2015 to Dec 2017 to explore the impact of the financial restatement on the idiosyncratic risk of stocks. Further, the financial restatement that has more media attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The enhancement of corporate value by media attention is also reflected in the impact on the stock value. Higher media coverage of corporate social responsibility behavior enhances the corporate value and stock returns, and the visibility of the behavior has a more pronounced effect on the corporate value for companies that are actively involved in social responsibility activities [16], and stocks with high media attention are more likely to receive consistently high levels of investor attention, which leads to higher returns over time [17]. In addition, Kang et al [18] found that media coverage showed a significant negative relationship with the risk of stock price collapse.…”
Section: A Review Of Relevant Research On Media Attentionmentioning
confidence: 99%
“…The enhancement of corporate value by media attention is also reflected in the impact on the stock value. Higher media coverage of corporate social responsibility behavior enhances the corporate value and stock returns, and the visibility of the behavior has a more pronounced effect on the corporate value for companies that are actively involved in social responsibility activities [16], and stocks with high media attention are more likely to receive consistently high levels of investor attention, which leads to higher returns over time [17]. In addition, Kang et al [18] found that media coverage showed a significant negative relationship with the risk of stock price collapse.…”
Section: A Review Of Relevant Research On Media Attentionmentioning
confidence: 99%
“…Furthermore, the management's honesty and competency are being called into question. When fraud is involved, the consequences are magnified (Yin & Sun, 2021). When a company's stock price falls below a certain threshold, it may be forced to declare bankruptcy and be delisted from the national stock exchange (Murhadi, 2010).…”
Section: Problem Statementmentioning
confidence: 99%
“…The board of directors generally has a short duration and the financial restatement behavior is hidden, which requires the board to effectively deal with fraudulent decisions . Second, the higher the clarity of the informal hierarchy of the board of directors, the more it can enhance communication and exchange among board members, create an environment of mutual checks and balances for the board of directors, enhance the overall cohesion of the board of directors, maintain the independence of the board of directors, avoid the board of directors being "captured" by managers, and increase the cost of "collusion" between managers and board members (Yi & Sun, 2022). It also helps to avoid the "capture" of the board of directors by managers, increase the cost of "collusion" between managers and board members, strengthen the board of directors' supervision of managers, inhibit managers' self-interest in the process of financial restatement behavior, and reduce the financial restatement behavior of enterprises.…”
Section: Board Informal Hierarchy and Corporate Financial Restatement...mentioning
confidence: 99%